Will robots make good perioperative nurses? - Jed Duff (Journal of Perioperative Nursing)
New technology is always being introduced into health care and nursing as a profession has had to adapt. Technological advances have changed the practice of nursing from the introduction of the stethoscope to the electronic health record, and now robots and artificial intelligence (AI). With technological advancements occurring at an ever-increasing rate, more and more perioperative tasks will be delegated to robots and AI. The main question for perioperative nurses is, how can we remain relevant in the high-tech operating room of the future?